Small-World Networks of corruption (2016)
Collective behavior forms and spreads through social contact. This thesis introduces a framework for understanding how the structure of social ties may impact the evolution of bribery. We represent relationships as highly clustered networks with small characteristic path lengths (i.e., small-world models having “local” and “long-range” contacts). Based on a principal-agent-client formulation, our model focuses on the effects of clustering on an equilibrium of persistent bribery. Collective outcomes depend on decision-making mechanisms that rely on sensitivity functions, which capture the level of influence between local contacts. Moreover, we represent the evolution of the network as a system of differential equations and identify its region of parameters for which the equilibrium of persistent bribery is stable. Our results show that an increase in clustering tends to decrease the levels of bribery. A more sensitive response to the behavior of neighbors, on the other hand, tends to increase bribery, but only up to a certain point. Beyond this threshold, the expected level of bribery remains constant, despite variations in the structural properties of the network.